Model Bleanded Learning Dipadukan dengan Tanya Jawab untuk Meningkatkan Aktivitas dan Prestasi Belajar Agama Hindu dan Budi Pekerti Siswa Kelas XI SMK TI Bali Global Singaraja - Desi Mardana, I Kadek; Tari Karismayanti, Komang; Endra Suwantara, I Nengah Dwi (Jurnal Widya Sastra Pendidikan Agama Hindu, 2023)
Education is an important activity in the progress of mankind. Education is basically always related between two parties, namely educators and students. However, the phenomenon faced by Class XI TKJ students of Ti Bali Global Singaraja Vocational School is the problem of low activity and achievement in the field of Hinduism and Moral Character. The purpose of this study was to find out "The application of blended learning combined with question and answer to increase learning activity and achievement in Hinduism and Virtue Education for Class XI TKJ students of TI Bali Global Singaraja Vocational School in the 2021/2022 academic year". The research subjects in this study were all students of class XI who were Hindus.This research was conducted in two cycles with data collection techniques through observation, interviews, administering tests which were processed using quantitative descriptive analysis.